Bisphenol A (BPA) and Cardiovascular or Cardiometabolic Diseases - Jeong-Hun Kang; Daisuke Asai; Riki Toita (Journal of Xenobiotics, 2023)
Bisphenol A (BPA; 4,4′-isopropylidenediphenol) is a well-known endocrine disruptor. Most human exposure to BPA occurs through the consumption of BPA-contaminated foods. Cardiovascular or cardiometabolic diseases such as diabetes, obesity, hypertension, acute kidney disease, chronic kidney disease, and heart failure are the leading causes of death worldwide. Positive associations have been reported between blood or urinary BPA levels and cardiovascular or cardiometabolic diseases. BPA also induces disorders or dysfunctions in the tissues associated with these diseases through various cell signaling pathways. This review highlights the literature elucidating the relationship between BPA and various cardiovascular or cardiometabolic diseases and the potential mechanisms underlying BPA-mediated disorders or dysfunctions in tissues such as blood vessels, skeletal muscle, adipose tissue, liver, pancreas, kidney, and heart that are associated with these diseases.